Factors Affecting Human Resource Information System: IT Infrastructure, Management Support, and Market Competition - Afif Maulana Ibrahim; Hapzi Ali (Dinasti International Journal of Management Science, 2023)
The effect of Infrastruktur Teknologi Informasi, Dukungan Manajemen and Kompetisi Pasar on Sistem Informasi Sumber Daya Manusia is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. The results of this article: 1) Infrastruktur Teknologi Informasi has an effect on Sistem Informasi Sumber Daya Manusia; 2) Dukungan Manajemen has an effect on Sistem Informasi Sumber Daya Manusia; and 3) Kompetisi Pasar has an effect on Sistem Informasi Sumber Daya Manusia.